Quality of life among Ardabil patients with beta-thalassemia major - Amani, Firouz; Fathi, Afshin; Valizadeh, Mehdi; Farzaneh, Esmaeil; Fattahzadeh-Ardalani, Ghasem (International Journal of Research in Medical Sciences, 2017)
Background: Thalassemia as the most common genetic disorder worldwide is regarded as a serious problem in public health issues in the Mediterranean region. Patients with beta-thalassemia major experience physical, psychological and social problems that lead to decreased quality of life. The aim of this study was to assess health-related quality of life and its determinants among patients with major beta-thalassemia. Methods: This was a population-based cross-sectional survey of quality of life. Population with thalassemia major (aged ≥ 2 years) of both genders who had records in Thalassemia Clinic of Bu-Ali Hospital, and those who regularly refer for blood transfusion or follow-up visits. Data were collected from December 2013 to May 2014.The self-administered short form-36 (SF-36) questionnaire was used to measure quality of life in patients with thalassemia. Data were analysed using descriptive statistical tests (mean, SD, and frequency), and inferential statistical test (t-test) in SPSS.17 software. Results: Our samples were 20 men and 23 women. The median age was 20 years (2-42). After reviewing the patients' quality of life, it was observed that the mean score for physical function was 79.8, role limitations due to physical reasons 78.8, bodily pain 74.4, general health 59.1, fatigue or vitality 63.3, social function 70.21, role limitations due to psychological reasons (emotional) 77.3 and mental health 65.4. On two scales, role physical (P = 0.33) and role emotional (P = 0.13), the men showed significantly lower scores than the women. Conclusions: After reviewing the patients' quality of life, the highest quality in physical function and lowest quality in general health of patients were observed. In the quality of care data all scales were in very good level except general health.